Oral polio revaccination is associated with changes in gut and upper respiratory microbiomes of infants - Medeiros, Márcia Melo; Ingham, Anna Cäcilia; Nanque, Line Møller; Correia, Claudino; Stegger, Marc; Andersen, Paal Skyt; Fisker, Ane Baerent; Benn, Christine Stabell; Lanaspa, Miguel; Silveira, Henrique; Abrantes, Patrícia (Frontiers in Microbiology, 2022)
After eradication of polio infection, the plan is to phase-out the live-attenuated oral polio vaccine (OPV). Considering the protective non-specific effects (NSE) of OPV on unrelated pathogens, the withdrawal may impact child health negatively. Within a cluster-randomized trial, we carried out 16S rRNA deep sequencing analysis of fecal and nasopharyngeal microbial content of Bissau-Guinean infants aged 4 to 8 months, before and after 2 months of OPV revaccination (revaccinated infants=47) versus no OPV revaccination (control infants=47). The aim was to address changes in gut and upper respiratory bacterial microbiotas due to revaccination. Alpha-diversity for both microbiotas increased similarly over time in OPV revaccinated infants and controls, whereas greater changes over time in bacterial composition of gut (padjusted<0.001) and upper respiratory microbiotas (padjusted=0.018) were observed in the former. Taxonomic analysis of gut bacterial microbiota revealed a decrease over time in median proportion of Bifidobacterium longum for all infants (25% to 14.3%, p=0.0006 in OPV-revaccinated infants and 25.3% to 11.6%, p=0.01 in controls), compatible with the reported weaning. Also, it showed a restricted increase in median proportion of Prevotella_9 genus in controls (1.4% to 7.1%, p=0.02), whereas in OPV revaccinated infants an increase over time in Prevotellaceae family (7.2% to 17.4%, p=0.005) together with a reduction in median proportion of potentially pathogenic/opportunistic genera such as, Escherichia/Shigella (5.8% to 3.4%, p=0.01) were observed. Taxonomic analysis of upper respiratory bacterial microbiota revealed an increase over time in median proportions of potentially pathogenic/opportunistic genera in controls, such as Streptococcus (2.9% to 11.8%, p=0.001 and Hemophilus (11.3% to 20.5%, p=0.03), not observed in OPV revaccinated infants. In conclusion, OPV revaccination was associated with a healthier microbiome composition 2 months after revaccination, based on a more abundant and diversified bacterial community of Prevotellaceae and fewer pathogenic/opportunistic organisms. Further information on species-level differentiation and functional analysis of microbiome content are warranted to elucidate the impact of OPV-associated changes in bacterial microbiota on child health.